Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.2118/122137-pa
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of Residual Oil on Particle Trapping During Produced-Water Reinjection Using X-Ray Tomography

Abstract: Summary Recently, it has been shown that the presence of residual oil in a formation can have a considerable influence on the trapping mechanisms for particles present in reinjected produced water (Ali 2007; Ali et al. 2005, 2007, 2009). This article reports on a further set of extensive coreflow experiments that confirm and extend these results. The tests were conducted in a computerized-tomography (CT) scanner, allowing direct observation of the buildup of particle deposition along the core. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The next step must include colloid injections into natural reservoir cores. Additional validation of the proposed model can be performed by measuring the retention profile (see Ali et al 2009;Saraf et al 2010). Yet, the experimental technique involving a computer-tomography (CT) scanner becomes much more complex than that used in the presented study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The next step must include colloid injections into natural reservoir cores. Additional validation of the proposed model can be performed by measuring the retention profile (see Ali et al 2009;Saraf et al 2010). Yet, the experimental technique involving a computer-tomography (CT) scanner becomes much more complex than that used in the presented study.…”
Section: Discussionmentioning
confidence: 99%
“…The rock alteration in the preceding processes is a result of particle capture by the matrix, which leads to permeability damage. Such capture is caused by size exclusion of large particles, particle/ grain attachment, gravity segregation, particle diffusion into deadend pores, and bridging (Nabzar et al 1996;Chauveteau et al 1998;Rousseau et al 2008;Saraf et al 2010). The straining mechanism, in which large particles become stuck in thin pores (sizeexclusion capture), often occurs in formation-damage processes.…”
Section: Introductionmentioning
confidence: 99%
“…Suspension viscosity is generally described in terms of the viscosity of the continuous liquid phase l b and the amount of suspended material. The Einstein equation (Schramm 1996) for the viscosity of suspensions containing spherical particles is given by…”
Section: Model Formulationmentioning
confidence: 99%
“…Sun et al studied the oil displacement mechanism of continuous and dispersed phase flooding agents and found that SMG dispersion has better performance in increasing oil production and lowering water production. Bataweel et al , conducted research on the oil displacement mechanism of cross-linked polymer using the computed tomography (CT) technique. Hellevang et al. presented CO 2 enhanced oil recovery (EOR) mechanism in low-pressure, low-porosity, and low-permeability reservoirs.…”
Section: Introductionmentioning
confidence: 99%